The method of the likelihood and the Fisher information in the construction of physical models - Piotrowski, E.W.; Sładkowski, J.; Syska, J.; Zaja̧c, S. (Physica Status Solidi (b), 2009)
The subjects of the paper are the likelihood method (LM) and the expected Fisher information (FI) considered from the point od view of the construction of the physical models which originate in the statistical description of phenomena. The master equation case and structural information principle are derived. Then, the phenomenological description of the information transfer is presented. The extreme physical information (EPI) method is reviewed. As if marginal, the statistical interpretation of the amplitude of the system is given. The formalism developed in this paper would be also applied in quantum information processing and quantum game theory (© 2009 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)